"The path is made by walking”: experience of mental health league members (Citizenship in Action: Extension and Culture Magazine, 2023)
The objective was to report the experience of students who participated in the Interdisciplinary League in Mental Health. This is an experience report carried out with 35 students who participated in the League. The statements were organized into five categories of analysis: experiences lived by the League members; potentialities of academic leagues in the student training process; articulation among the three university tripod axes: extension, teaching, and research; development of social and emotional skills; and project deadlocks and limitations. League members explained everything from intricate learning regarding mental health to experiences through the League's community extensions. The reports express great academic development, acquiring skills and competencies built from teaching, research, and extension. We can conclude that academic leagues contribute effectively to the training and qualification of future professionals.